26 Exenatide alleviate adriamycin-induced cardiac injury. (October 2018) - Juntao, F; Lijuan, W; Xiaoman, Z; Shangyu, L; Hui, L; Tiewei, L; Ping, L
Abstract : Introduction: Adriamycin (ADR) is an effective antitumor drug, which is limited due to its lethal cardiac injury in clinical application. Exenatide (Exe) is a glucagon-like peptide-1 (GLP-1) analog, it can not only regulate blood glucose, but protect the myocardium by reducing inflammation, oxidative stress and cell apoptosis. Since adriamycin-induced cardiac injury is currently thought to be mainly caused by inflammation, oxidative stress and cell apoptosis, we hypothesized that prophylactic treatment with exenatide may alleviate adriamycin-induced cardiac injury. Methods: In vitro experiments, we divided H9C2 cells into control group, adriamycin group and exenatide intervention group. After starvation of H9C2 cells for 24 hour, the adriamycin group was given adriamycin (10 uM) for 24 hour, and the exenatide intervention group was pretreated with exenatide (30 nM) half an hour before adriamycin administration. After treatment, CCK-8 and Annexin V/PI staining were used to detect H9C2 cells activity and apoptosis. In vivo experiments, we randomly assigned 18 C57BL/6J mice to control group, adriamycin group and exenatide intervention group (n=6 each). Adriamycin group was intraperitoneally injected with adriamycin (2 mg/kg), exenatide intervention group was given subcutaneous injection of exenatide (5 µg/kg) 1 hour before adriamycin injection, and the control group was given only equal volume of Normal saline. After treatment, echocardiography was performed to evaluate exenatide-induced changes in cardiac performance on the 20th day after beginning ADR administration, and the levels of LDH, CK-MB, SOD and MDA in plasma were observed. The mRNA expression of TNF-α, IL-6, Bcl-2 and Bax in myocardial tissue were detected by RT-PCR. The protein expression levels of NF-κB and P53 in myocardial tissue were detected by Western Blot. Results: In vitro, compared with the control group, the H9C2 cells activity in the adriamycin group was significantly decreased (p<0.001). In addition, the number of Annexin V+/PI— and Annexin V+/PI +cells increased from 16.7% (control group) to 73.1% after adriamycin administration (p<0.001). Compared with adriamycin group, the activity of H9C2 cells in the exenatide intervention group was significantly increased (p<0.01), and the number of Annexin V+/PI— and Annexin V+/PI +cells decreased to 29.5% (p<0.01). In vivo experiment, compared with the control group, the mice in the adriamycin group had significantly reduced ejection fraction (p<0.01) and fractional shortening (p<0.01) values on the 20th day, and the LDH, CK-MB, and MDA levels in plasma of the adriamycin group were significantly increased (All were p<0.01), and the SOD level was significantly decreased (p<0.01). Compared with the adriamycin group, mice in the exenatide intervention group were found to have recovered cardiac function (All were p<0.05), and the LDH, CK-MB, and MDA levels in plasma were significantly decreased in the exenatide intervention group (both CK-MB and MDA were p<0.01, LDH was p<0.05), and SOD level was significantly increased (p<0.05). In addition, compared with the control group, the mRNA expression level of Bcl-2 in the adriamycin group was significantly decreased (p<0.01), and the mRNA expression levels of Bax, TNF-α, and IL-6 were significantly increased (All were p<0.01), the protein expression levels of NF-κB and P53 were also significantly increased (All were p<0.05). Compared with adriamycin group, the mRNA expression level of Bcl-2 was significantly increased in exenatide intervention group (p<0.05), and the mRNA expression levels of Bax, TNF-α and IL-6 were significantly decreased (All were p<0.05), the protein expression levels of NF-κB and P53 were also significantly decreased (All were p<0.05). Conclusion: Exenatide can alleviate adriamycin-induced cardiac injury through the reduction of oxidative stress, inflammation and cell apoptosis